Raman imaging of microplastics and nanoplastics released from the printed toner powders burned by a mimicked bushfire - Luo, Yunlong; Zhang, Zixing; Naidu, Ravi; Zhang, Xian; Fang, Cheng (The Science of the total environment, 2022)
Plastic contamination is a growing global concern, but the characterisation approaches for microplastics are limited so far, and even more lacking for nanoplastics. As another public concern, bushfire has the potential to exacerbate the negative ecological effects of plastic waste. We thus study the release of microplastics and nanoplastics from toner powers printed on a paper sheet following a mimicked bushfire. The results show that, along the fire frontier, there is a charred area first, then a cindered area towards mineralisation via a full combustion. We find that, depending on the extent of burning, the printed toner powers containing microplastics can melt to aggregate, or crack to break down to nanoplastics, which are well characterised by mass spectrometry and Raman imaging combined with algorithms. Overall, the results shed new light on the microplastics and nanoplastics once affected by bushfire. [Display omitted] •Microplastics and nanoplastics are detected after burning of printed paper.•PCA algorithm enhances identification of weak signals during Raman imaging.•Nanoplastics can be released by breaking the microplastics, once burned by bushfire.•Bushfire might promote microplastic and nanoplastic contamination.•The fate of microplastics generated in a bushfire should be researched more.